How Important are Foreign Banks in the Financial Development of European Transition Countries? - Ilko Naaborg; Bert Scholtens; Jakob de Haan; Hanneke Bol; Ralph de Haas (Center for Economic Studies and ifo Institute (CESifo), 2003)
This paper analyzes the development of the banking sector in European transition countries. We find that, although bank assets increased during the 1990s, credit to the private sector remained relatively low. Foreign-owned banks have become major players in the financial system of these countries. However, foreign bank presence and financial development in general vary considerably among the transition economies. Foreign-owned banks have, in general, higher profitability levels than domestic banks. Furthermore, it appears that foreign and domestic bank performance tend to converge.
Keywords: 330; financial development; financial institutions; foreign bank entry; transition economies; bank performance